Profile of children, adolescents and their caregivers assisted by a Home Care Program - Fernanda Elisa Pereira Mariani; Elysângela Dittz Duarte; Bruna Figueiredo Manzo (Universidade Federal do Ceará, 2016)
Objective: to identify the sociodemographic and clinical profile of children, adolescents and caregivers assisted by a Home Care Program. Methods: a descriptive, exploratory and retrospective study of quantitative approach. 42 medical records data from patients aged between zero and 18 years were collected. Results: the population assisted in the program was predominantly male (61.9%), less than 6 years (59.5%) diagnosed with neurological diseases (40.0%). Most patients had up to ten visits of the multidisciplinary team (40.5%), those patients remained in the Home Care Program for 6 months. Regarding therapeutic procedures, 42.9% of the patients underwent gastrostomy and 31.0% underwent tracheostomy. As for the caregivers, 95% were women, and of these, 52.4% did not work. Conclusion: the main conditions of health and the care required during the hospitalization by the program were identified, which require training of the health professionals to perform this task at home.